Higher Antineutrophil Cytoplasmic Antibody (C-ANCA) Titers are Associated with Increased Overall Healthcare Use in Patients with Sinonasal Manifestations of Granulomatosis with Polyangiitis (GPA). Issue 3 (May 2015) - Janisiewicz, Agnieszka M.; Klau, Marc H.; Keschner, David B.; Lehmer, Randy R.; Venkat, Kumar V.; Medhekar, Swati S.; Chang, Parke K.; Badran, Karam; Leary, Ryan; Garg, Rohit; Nguyen, Andrew A.; Lee, Jivianne T.
Background: Granulomatosis with polyangiitis (GPA) is an autoimmune disease characterized by necrotizing granulomatous airway inflammation and vasculitis. Sinonasal involvement occurs in more than 80% cases, with antineutrophil cytoplasmic antibody (C-ANCA) titers used as a marker of disease severity. The purpose of this study was to determine whether C-ANCA levels impact radiographic findings and healthcare use in patients with sinonasal GPA. Methods: A retrospective review was performed on GPA patients evaluated in a multidisciplinary rheumatologic/otolaryngologic clinic from 2008 to 2013. Data were collected with respect to age, gender, clinical presentation, C-ANCA titers, Lund-Mackay (LM) scores, surgical interventions, and healthcare use, the latter of which were determined by assessing the number of rheumatology/otolaryngology clinic visits, computed tomography (CT) scans, and email/telephone encounters. Results: A total of 44 patients were identified, 11 male and 33 female. Sinonasal manifestations were evident in 70.4%, with chronic rhinosinusitis (CRS) (41.9%), septal perforation (38.7%), and crusting (32.2%) the most common findings. No significant differences in number of CT scans (p = 0.10) or mean LM scores (p = 0.47) were found between patients with more than or equal to 1:80 and less than 1:80 C-ANCA titers, respectively. However, overall healthcare use was increased in the more than or equal to 1:80 C-ANCA group (n = 28) compared with less than 1:80 (n = 16), with a significantly greater number of rheumatologic/otolaryngologic encounters (mean 121 versus 69.2, p = 0.03) noted. When otolaryngologic healthcare use was specifically examined, the average number of encounters was also higher in more than or equal to 1:80 C-ANCA patients (31.9 versus 22.9), but this difference was not statistically significant (p = 0.16). Conclusion: Sinonasal GPA patients with presenting C-ANCA titers more than or equal to 1:80 demonstrated significantly greater overall healthcare use than their lower C-ANCA level counterparts (less than 1:80). However, no significant differences in otolaryngology resource use or LM scores were evident between the two titer groups.